Isolation of Flavonoids Compounds from Kesumba Keling Leaves (Bixa orellana L.) - Lenny, Sovia; Sihombing, Debynati; Marpaung, Lamek (Talenta Publisher, 2022)
Isolation of flavonoid compounds from leaves of Kesumba Keling (Bixa orellana L.). Extraction has been done with maceration by methanol solvent. The concentrated extract of methanol was added with ethyl acetate. The concentrated ethyl acetate extract was then dissolved with methanol and partitioned with n-hexane. The concentrated methanol extract was acidified by 6% HCl, then partition extracted with chloroform. The concentrated chloroform extract was separated by column chromatography with eluent n-hexane: ethyl acetate 90:10; 80:20; 70:30; 60:40; 50:50 (v/ v). The compounds were purified with TLC preparative yielding yellow gum weighing 29.7 mg with Rf=0.51. The compound was further identified by Ultraviolet-Visible spectroscopy (UV-Vis), Fourier Transform Infra Red Spectroscopy (FT-IR), and Proton Nuclear Magnetic Resonance Spectroscopy (1H-NMR). Spectroscopic data show that the compound was isoflavone.